Poverty measurement for a binational population - Pena, Anita Alves (Migration Letters, 2013)
Traditional poverty measures are inappropriate for migrant populations. Frequently cited poverty thresholds are calculated under assumptions that individuals and their families face only one set of prices annually. This study formulates (and contrasts to current thresholds) alternative measures for a population that spends substantial time in two (or more) countries. Specifically, weights are developed based on annual week allocations, income, family characteristics, and comparative price levels. As illustration, an example demonstrating how alternative thresholds can be generated for those whose annual work spans international boundaries is drawn from the Mexico-US migration context using survey data, official thresholds, and these weights. Despite caveats due to data limitations for the case study, illustrations should be of interest academically and to those involved in ground-level statistical calculations pertaining to demographic trends and the welfare state.